Surgical management of uterine prolapse by sacrohysteropexy: a case series - Moharana, Manas R.; Pati, Banishree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Abdominal sacrohysteropexy is a transabdominal procedure where the prolapsed uterus is suspended from the sacral promontory by the use of mesh to restore the normal anatomical position. The purpose of our study was to assess the safety of sacrohysteropexy surgery by determining intraoperative and post-operative complications and its effectiveness in management of UV prolapse by pelvic organ prolapse recurrence on follow up. A rospective study was carried out in the department of gynaecology and obstetrics, RIMS medical college, Raipur, Chhattisgarh from January 2023 to December 2023. Eight young patients <40 years of age with 2nd degree or more uterovaginal prolapse, admitted through OPD were selected for abdominal sacrohysteropexy with polypropelene mesh. Variables of study including duration of surgery, any intra-operative and post operative complications, need of intra operative blood transfusion, post operative hospital stay; recurrence of POP in 06 months follow up were recorded. In these 8 patients, mean age was 33.5 years. All were married with parity 2 or more and all of them had only vaginal deliveries and had 3rd degree pelvic organ prolapse (POP). Duration of surgery was around 90 mins. In our cases intra operative blood loss was around 250 ml. Post operatively no case developed any complications and all were discharged on 5th post operative day. No recurrence was noticed in 06 months follow up. Abdominal sacrohysteropexy is a safe and an effective surgical treatment in terms of overall anatomical and functional outcome, intraoperative and postoperative complications, post operative recovery and length of hospital stay in women who desire uterine and hence fertility preservation.